Arquitetura e instrução pública: a Reforma de 1922, concepção de espaços e formação de grupos escolares no Ceará - Santiago, Zilsa Maria Pinto (2011)
This research is in the field of Education History, specifically on culture of school material. It covers the formation of concepts of school buildings in Brazil, from the end of the 19th century to the first decades of the 20th century, specifically focused on the 1920’s and 1930’s, when there was social conflict between traditional and modern trends, in Architecture, as well as in Pedagogy, and also in Economy and Politics. The focus is on the 1922 public education reform process in the state of Ceará, as a condition for the establishment of educational spaces. This research highlights the contributions and changes due to this reform on the understanding of the meaning of a schoolhouse, questioning to what point schoolhouses built in this period, specifically in Fortaleza, were satisfying the ideal of modern education. The work analyses the period that preceded the 1922 Public Instruction Reform, from a comparative perspective, regarding various aspects and procedures, that involved a type of school and more representative school buildings; the study also reconstitutes the material memory of public elementary educational institutions in Ceará; and identified changes in architectural standards in schools, as well as factors related to educational equipment location in Cities. The study reveals that the educational organization called granular school of elementary education, characterized by multiple classrooms, with classes of various levels and one instructor for each class, first appeared in Ceará in the 1900’s; and its architectural materialization occurred with the creation of school groups, which emerged in the first two decades of the republication phase, more concentrated in the 1930’s. This research was based on printed documents and photographs, legislation, regulations and codes, as well as the History of Education and Architecture and, when possible, oral history. Three types of architectural concepts for educational buildings were identified: 1. buildings as a representation of erudite architecture; 2. “convenient” buildings; 3. “functional” or standard project buildings. There is an articulation of school space with teaching aspects and methods, even though there is evidence of oscillation in teaching, between the influence of Traditional Pedagogy and Active School, the latter being a modernizing trend in line a new national republican project, which would be created along with the fight for a New School, but would not be limited to this, specifically due to disputes between those that defended secular and confessional teaching. Keywords: History of Education. Educational architecture. Educational reform. School Groups.